Have a good day! An experience-sampling study of daily meaningful and pleasant activities - Kreiss, Christoph; Schnell, Tatjana (Frontiers in Psychology, 2022)
We organize our daily lives with a relatively high degree of freedom. Some things must be done; others are optional. Some we find meaningful, some pleasant, some both, and some neither. The present study looks at such evaluations of daily activities and how they relate to perceived meaning in life. Sixty-two students from an Austrian university first completed the meaningfulness scale from the Sources of Meaning and Meaning in Life Questionnaire (SoMe). They then participated in a one-week experience-sampling assessment, wherein they completed a short questionnaire at five random time-points per day. They indicated their current activity and then reported, on a 6-point Likert scale, how pleasant and meaningful they perceived it to be. Activities could thus be categorized as meaningful, pleasant, both, or neither; results reflected that activities grouped under culture/music, communication, intimacy, and sports are experienced as both highly meaningful and pleasant. An hierarchical linear regression suggested that people with high trait meaningfulness experience their daily activities as more meaningful than people with lower trait meaningfulness if they also enjoy what they are doing. People with low trait meaningfulness, however, tended to experience their daily activities as rather meaningless, even if they enjoyed them very much. Thus, when looking for advice on how to have a good day, clarifying one’s meaning in life seems to represent the best starting point.